Hemophagocytic syndrome: a dilemma chasing the intensivists - Adriana Façanha Queiroz; Gabriel Nuncio Benevides; Iracema de Cássia Oliveira Ferreira Fernandes; Patrícia de Freitas Goes; Albert Bousso; Cristiane Rúbia Ferreira (University of São Paulo, 2015)
Hemophagocytic lymphohistiocytosis or hemophagocytic syndrome is represented by an uncontrolled inflammatory response characterized by marked histiocyte activation and a cytokine storm. The entity may present a primary or genetic type, and the secondary type is usually triggered by infectious diseases of any kind, autoimmune disease, or neoplasia. This entity, although well described and with definite diagnostic criteria, still remains misdiagnosed because of the overlap presentation with other inflammatory processes. The authors present the case of a 13-year-old girl who was submitted to an appendicectomy complicated with a pericolic abscess, which required a second operation in order to be drained surgically. During the postoperative period of this second surgical procedure, the patient remained febrile, developing cytopenias, and multiple organ failure. Unfortunately, she died despite the efforts of the intensive care. The autopsy findings were characteristic of hemophagocytic syndrome. The authors report the case to call attention to this diagnosis whenever unexpected outcomes of infections are experienced.